Impaired inflammatory pain and thermal hyperalgesia in mice expressing neuron-specific dominant negative mitogen activated protein kinase kinase (MEK) - Kaplan David; Adwanikar Hita; Hu Hui-Juan; Karim Farzana; Gereau Robert W (SAGE Publishing, 2006)
Abstract Background Numerous studies have implicated spinal extracellular signal-regulated kinases (ERKs) as mediators of nociceptive plasticity. These studies have utilized pharmacological inhibition of MEK to demonstrate a role for ERK signaling in pain, but this approach cannot distinguish between effects of ERK in neuronal and non-neuronal cells. The present studies were undertaken to test the specific role of neuronal ERK in formalin-induced inflammatory pain. Dominant negative MEK (DN MEK) mutant mice in which MEK function is suppressed exclusively in neurons were tested in the formalin model of inflammatory pain. Results Formalin-induced second phase spontaneous pain behaviors as well as thermal hyperalgesia measured 1 - 3 hours post-formalin were significantly reduced in the DN MEK mice when compared to their wild type littermate controls. In addition, spinal ERK phosphorylation following formalin injection was significantly reduced in the DN MEK mice. This was not due to a reduction of the number of unmyelinated fibers in the periphery, since these were almost double the number observed in wild type controls. Further examination of the effects of suppression of MEK function on a downstream target of ERK phosphorylation, the A-type potassium channel, showed that the ERK-dependent modulation of the A-type currents is significantly reduced in neurons from DN MEK mice compared to littermate wild type controls. Conclusion Our results demonstrate that the neuronal MEK-ERK pathway is indeed an important intracellular cascade that is associated with formalin-induced inflammatory pain and thermal hyperalgesia.